Vigabatrin with hormonal treatment versus hormonal treatment alone (ICISS) for infantile spasms: 18-month outcomes of an open-label, randomised controlled trial - O'Callaghan, Finbar; Rating, Dietz (The lancet child & adolescent health, 2018)
Background - Infantile spasms constitute a severe form of epileptic encephalopathy. In the International Collaborative Infantile Spasms Study (ICISS), we showed that combining vigabatrin with hormonal therapy was more effective than hormonal therapy alone at stopping spasms between days 14 and 42 of treatment. In this planned follow-up, we aimed to assess whether combination therapy was associated with improved developmental and epilepsy outcomes at 18 months of age. - Methods - In ICISS, a multicentre, open-label, randomised controlled trial, infants were enrolled from 102 hospitals (three in Australia, 11 in Germany, two in New Zealand, three in Switzerland, and 83 in the UK). Eligible infants had a clinical diagnosis of infantile spasms and a hypsarrhythmic (or similar) electroencephalogram (EEG) no more than 7 days before enrolment. Participants were randomly assigned (1:1) by a secure website to receive hormonal therapy with vigabatrin or hormonal therapy alone. If parents consented, there was an additional randomisation (1:1) of type of hormonal therapy used (prednisolone or tetracosactide depot). Block randomisation was stratified for hormonal treatment and risk of developmental impairment. Parents and clinicians were not masked to therapy, but investigators assessing epilepsy and developmental outcomes at 18 months were masked to treatment allocation. Minimum doses were oral prednisolone 10 mg four times a day or intramuscular tetracosactide depot 0·5 mg (40 IU) on alternate days with or without oral vigabatrin 100 mg/kg per day. The primary outcome at 18 months was development as assessed by the Vineland Adaptive Behaviour Scales (VABS) composite score. Secondary outcomes were the presence or absence of epileptic seizures or infantile spasms in the previous 28 days, as recorded by parents and carers, and the use of any anti-epileptic treatment (including ketogenic diet) in the previous 28 days. Analysis was by intention to treat. The trial is registered with the ISRCTN registry, number 54363174, and EudraCT, number 2006-000788-27. - Findings - Between March 7, 2007, and May 22, 2014, 766 infants were screened and, of those, 377 were randomly assigned to hormonal therapy with vigabatrin (n=186) or hormonal therapy alone (n=191). 362 infants were assessed for developmental and epilepsy outcomes at 18 months, 181 in each treatment group. Mean VABS scores did not differ significantly between the combination therapy group and the hormonal therapy alone group (73·9 [SE 1·3] vs 72·7 [1·4], difference −1·2 [95% CI −4·9 to 2·6], p=0·55). Presence of epilepsy at the assessment at age 18 months was similar in both treatment groups (54 [30·0%] of 180 infants who received combination therapy vs 52 [29·2%] of 178 who received hormonal therapy alone; difference 0·8% [95% CI −8·8 to 10·4], p=0·90). Presence of spasms was also similar in both treatment groups (27 [15·0%] of 180 infants on combination therapy vs 28 [15·7%] of 178 on hormonal therapy alone; difference 0·7% [95% CI −6·9 to 8·3], p=0·85). At the 18-month assessment, 158 (44·1%) of 358 infants were on some form of anti-epileptic treatment. Initial control of spasms between days 14 and 42 of treatment was associated with higher mean VABS scores at 18 months (79·1 [SE 1·2] vs 63·2 [1·1], difference 15·9 [95% CI 12·4 to 19·5], p<0·001) and with higher likelihood of absence of seizures at 18 months (in 39 [17·0%] of 229 infants who achieved spasm cessation vs 67 [51·9%] of 129 who did not; difference 34·9% [24·8 to 45·0], p<0·001). Increasing lead-time to treatment was associated with lower VABS scores (analysis of variance: F[4,354]=6·38, p<0·001) and worse epilepsy outcomes (p=0·023). - Interpretation - Combination therapy did not result in improved developmental or epilepsy outcomes at 18 months. However, early clinical response to treatment was associated with improved developmental and epilepsy outcomes at 18 months. Longer lead-time to treatment was associated with poorer outcomes. Rapid diagnosis and effective treatment of infantile spasms could therefore improve outcomes. - Funding - The Castang Foundation, Bath Unit for Research in Paediatrics, National Institute of Health Research, the Royal United Hospitals Bath NHS Foundation Trust, BRONNER-BENDER Stiftung/Gernsbach, University Children's Hospital Zurich.
Gesehen am 25.03.2020